The Evidence Base for the Benefits of Functional Septorhinoplasty and its Future Post COVID-19 - Unadkat, Samit N.; Pendolino, Alfonso Luca; Auer, Deborah; Khwaja, Sadie; Randhawa, Premjit S.; Andrews, Peter J.; Saleh, Hesham A. (Facial Plastic Surgery, 2021)
Ever since the introduction of the concept of Procedures of Limited Clinical Value (PoLCV), procedures such as functional septorhinoplasty have been subject to additional funding restrictions within the British National Health Service. Recent publications have suggested that 10% of Clinical Commissioning Groups in the United Kingdom no longer fund septorhinoplasty surgery irrespective of the indications, including congenital malformations or post-trauma, and despite the strong evidence available in the literature in treating a range of health conditions. Thus, inequity exists across the country. At present functional septorhinoplasty surgery is frequently but incorrectly grouped together with aesthetic rhinoplasty, both of which are deemed to be cosmetic interventions. Moreover, as we exit the peak of the current coronavirus disease 2019 (COVID-19) pandemic, procedures deemed to be of lower clinical priority will potentially be at risk throughout Europe. The purpose of this review is twofold; the first is to put forward the evidence to commissioners in favor of functional septorhinoplasty surgery on patient well-being and mental health; the second is to demonstrate why functional septorhinoplasty surgery is a distinct procedure from aesthetic rhinoplasty and why it ought not to be classified as a procedure of limited clinical value.
Keywords: evidence-based medicine; nasal obstruction; nasal septum; rhinoplasty; sleep apnea; obstructive